ESDN inhibits melanoma progression by blocking E-selectin expression in endothelial cells via STAT3. (10th July 2021) - Coppo, Roberto; Orso, Francesca; Virga, Federico; Dalmasso, Alberto; Baruffaldi, Desirée; Nie, Lei; Clapero, Fabiana; Dettori, Daniela; Quirico, Lorena; Grassi, Elena; Defilippi, Paola; Provero, Paolo; et al.
Abstract: An interactive crosstalk between tumor and stroma cells is essential for metastatic melanoma progression. We evidenced that ESDN/DCBLD2/CLCP1 plays a crucial role in endothelial cells during the spread of melanoma. Precisely, increased extravasation and metastasis formation were revealed in ESDN-null mice injected with melanoma cells, even if the primary tumor growth, vessel permeability, and angiogenesis were not enhanced. Interestingly, improved adhesion of melanoma cells to ESDN-depleted endothelial cells was observed, due to the presence of higher levels of E-selectin transcripts/proteins in ESDN-defective cells. In accordance with these results, anticorrelation was observed between ESDN and E-selectin in human endothelial cells. Most importantly, our data revealed that cimetidine, an E-selectin inhibitor, was able to block cell adhesion, extravasation, and metastasis formation in ESDN-null mice, underlying a major role of ESDN in E-selectin transcription upregulation, which according to our data, may presumably be linked to STAT3. Based on our results, we propose a protective role for ESDN during the spread of melanoma and reveal its therapeutic potential. Highlights: ESDN/DCBLD2/CLCP1 in endothelial cells regulates adhesion, extravasation and metastatization of melanoma cells. Melanoma cells adhere more to ESDN-depleted endothelial cells. Increased E-selectin expression in ESDN-depleted cells favours melanoma adhesion to endothelial cells and extravasation. ESDN regulates E-selectin transcription via STAT3.